Sexual selection and mating systems - Shuster, Stephen M. (National Academy of Sciences, 2009)
Sexual selection is among the most powerful of all evolutionary forces. It occurs when individuals within one sex secure mates and produce offspring at the expense of other individuals within the same sex. Darwin was first to recognize the power of sexual selection to change male and female phenotypes, and, in noting that sexual selection is nonubiquitous, Darwin was also first to recognize the importance of mating system—the “special circumstances” in which reproduction occurs within species. Analyses of mating systems since Darwin have emphasized either the genetic relationships between male and female mating elements, usually among plants, or the numbers of mates males and females may obtain, usually among animals. Combining these schemes yields a quantitative methodology that emphasizes measurement of the sex difference in the variance in relative fitness, as well as phenotypic and genetic correlations underlying reproductive traits that may arise among breeding pairs. Such information predicts the degree and direction of sexual dimorphism within species, it allows the classification of mating systems using existing genetic and life history data, and with information on the spatial and temporal distributions of fertilizations, it may also predict floral morphology in plants. Because this empirical framework identifies selective forces and genetic architectures responsible for observed male-female differences, it compliments discoveries of nucleotide sequence variation and the expression of quantitative traits. Moreover, because this methodology emphasizes the process of evolutionary change, it is easier to test and interpret than frameworks emphasizing parental investment in offspring and its presumed evolutionary outcomes.